A comparison of variability between absolute and relative blood flow restriction pressures. (21st April 2022) - Stanford, Daphney M.; Chatlaong, Matthew A.; Miller, William M.; Mouser, J. Grant; Dankel, Scott J.; Jessee, Matthew B.
Abstract: Introduction: Recommendations are that blood flow restriction (BFR) be applied relative to arterial occlusion pressure (AOP) to provide a similar stimulus. Purpose: Compare variability of the change in blood flow, shear rate and discomfort between recommended relative pressures and an absolute pressure. Methods: During one visit, brachial arterial blood flow was measured in 91 participants using pulse‐wave Doppler ultrasonography. After 5‐min seated rest, AOP was measured. Following another 5‐min rest, blood flow and discomfort were assessed twice before cuff inflation as controls (C1 and C2), then again with a cuff inflated to each BFR pressure (all measures separated by 1‐min). Change scores from C1 to all subsequent measures were calculated (i.e., C2‐C1; 40% AOP‐C1; 80% AOP‐C1; 100 mmHg‐C1). Variability of the changes were compared via pairwise modified Pitman–Morgan tests ( α = 0.008). Results: Variance (95% CI) of the change for blood flow (ml/min), shear rate (1/s), and discomfort (AU) had similar trends. C2‐C1 differed from all conditions (all p < 0.001), 40% AOP‐C1 differed from 80% AOP‐C1 and 100 mmHg‐C1 (all p < 0.001), which did not differ (both p ≥ 0.117). Blood flow: C2‐C1 = 469.79 (357.90, 644.07), 40% AOP‐C1 = 1263.18 (962.34, 1731.80), 80% AOP‐C1 = 1752.90 (1335.42, 2403.18), 100 mmHg‐C1 = 1603.18 (1221.36, 2197.92); shear rate: C2‐C1 = 6248.24 (4760.10, 8566.15), 40% AOP‐C1 = 14 625.30 (11 142.06, 20 050.95), 80% AOP‐C1 = 22 064.02 (16 809.13, 30 249.27), 100 mmHg‐C1 = 20 778.76 (15 829.98, 28 487.21); discomfort: C2‐C1 = 0.07 (0.05, 0.08), 40% AOP‐C1 = 2.03 (1.55, 2.78), 80% AOP‐C1 = 4.26 (3.25, 5.84), 100 mmHg‐C1 = 4.50 (3.43, 6.17). Conclusion: Contrary to previous suggestions, applying relative pressures does not necessarily guarantee a similar stimulus. It seems that higher pressures produce more variable changes even if the external pressure applied is made relative to each individual.